Firm Characteristics, Economic Conditions and Capital Structure Adjustment - Wolfgang Drobetz; Pascal Pensa; Gabrielle Wanzenried (University of Basel, Center of Business and Economics (WWZ), 2007)
We use a dynamic framework and panel methodology to investigate the determinants of a firms' time-varying capital structure. Our sample comprises 706 European firms from France, Germany, Italy and the U.K. over the period from 1983 to 2002. If capital structure adjustment is costly, firms may deviate temporarily from their target debt ratios. Therefore, we endogenize the adjustment process and analyze the impact of firm-specific characteristics as well as macroeconomic factors on the speed of adjustment towards target leverage. We find that larger and faster growing firms as well as firms that are further away from their targets adjust more readily. Additionally, we document interesting relations between well-known business cycle variables and the adjustment speed. In a nutshell, firms adjust faster in favorable macroeconomic conditions, e.g., if interest rates are low and the risk of disruptions in the global financial system are negligible. We also document that capital structure decision are largely determined by financial constraints. Finally, we shed new light on the interdependence between book value based and market value based measures of leverage as well as on capital structure rebalancing issues.
Keywords: G32; C61; C23; 330; Capital Structure; dynamic analysis; panel data; Kapitalstruktur; Betriebliche Kennzahl; Konjunktur; Panel; Schätzung; Frankreich; Deutschland; Italien; Großbritannien